2015
DOI: 10.1016/j.molcel.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The Menu of Features that Define Primary MicroRNAs and Enable De Novo Design of MicroRNA Genes

Abstract: Summary MicroRNAs (miRNAs) are small regulatory RNAs processed from stem-loop regions of primary transcripts (pri-miRNAs), with the choice of stem-loops for initial processing largely determining what becomes a miRNA. To identify sequence and structural features influencing this choice, we determined cleavage efficiencies of >50,000 variants of three human pri-miRNAs, focusing on the regions intractable to previous high-throughput analyses. Our analyses revealed a mismatched motif in the basal stem region, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
329
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(354 citation statements)
references
References 41 publications
21
329
3
1
Order By: Relevance
“…S3B,C). This is consistent with earlier observations from the Kim group and recent findings by the Bartel group (Han et al 2006;Fang and Bartel 2015). Unexpectedly, we also observed two bulge-depleted regions in miRNA hairpins, located at positions ∼5-9 nt and ∼16-21 nt relative to apical loop, or ∼16-21 nt and ∼28-32 nt relative to the base of the hairpin, observable for both arms of the stem (Fig.…”
Section: Bulge Positions Control Hairpin Processingsupporting
confidence: 94%
See 3 more Smart Citations
“…S3B,C). This is consistent with earlier observations from the Kim group and recent findings by the Bartel group (Han et al 2006;Fang and Bartel 2015). Unexpectedly, we also observed two bulge-depleted regions in miRNA hairpins, located at positions ∼5-9 nt and ∼16-21 nt relative to apical loop, or ∼16-21 nt and ∼28-32 nt relative to the base of the hairpin, observable for both arms of the stem (Fig.…”
Section: Bulge Positions Control Hairpin Processingsupporting
confidence: 94%
“…For example, several studies have proposed that the Microprocessor complex efficiently processes hairpins with stem lengths of ∼33 nucleotides (nt) (Han et al 2006;Nguyen et al 2015). Another recent study has used a cell-free screen on more than 210,000 random mutations in three pri-miRNA hairpins and found that the most favored substrates of the Microprocessor complex are hairpins of ∼35 ± 1 nt in stem length (Fang and Bartel 2015). Apical loop sizes of 3-23 nt have been found to be compatible with processing (Zeng and Cullen 2003), with loop size of ≥10 nt proposed to allow efficient processing (Ma et al 2013).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous biochemical data, it has been proposed that Microprocessor cleaves at a distance of ~11-bp from the basal junction and at a distance of ~22-bp from the apical junction. Recent studies have identified four primary sequence determinants located in the pri-miRNA scaffold (UGUG element in apical loop, GHG (H = A, U or C) elements in the stem, and UG and CNNC elements in the basal ssRNA overhangs ( Figure 1B)) that contribute to cleavage specificity and efficiency [5], providing additional constraints on Microprocessor recognition.…”
mentioning
confidence: 99%